Application of the UTAUT Model in Measuring the Usage Intention of the CoreTax Application Among Corporate Taxpayers in South Sulawesi, Indonesia - Muhammad Reza Ramdani; S. Subhan; Andi Muara ArumBarkah (Golden Ratio of Mapping Idea and Literature Format, 2026)
The study aims to examine the factors influencing the intention to use the CoreTax application among corporate taxpayers in South Sulawesi, using the Unified Theory of Acceptance and Use of Technology (UTAUT). By measuring the influence of each factor, this study is expected to identify key barriers and enablers in the adoption process of the CoreTax technology. The research employs a quantitative approach, with data collected through questionnaires distributed to corporate taxpayers at several Tax Service Offices (KPP) in the South Sulawesi region. Data were analyzed using Structural Equation Modeling (SEM). The findings of this study indicate that taxpayers' perceptions of the effectiveness of tax reporting through CoreTax have a significant and positive influence on their intention to continue using the system. The ease of use of CoreTax also exhibits a positive and significant effect on taxpayers' intention to use the system. Social influence, including encouragement from tax officers, recommendations from fellow taxpayers, and support from policies implemented at tax offices, positively and significantly affects usage intention. In contrast, facilitating conditions—such as internet access, computer equipment, or technological infrastructure at tax offices do not significantly affect taxpayers' intention to use the system. Furthermore, mandatory regulation serves as a moderating factor, strengthening the relationship between the perceived usefulness of the system and usage intention. Mandatory regulation also reinforces the influence of perceived ease of use on taxpayers' intention to adopt and use the CoreTax system.